Boosting the Immune System, From Science to Myth: Analysis the Infosphere With Google - Cassa Macedo, Arthur; Oliveira Vilela de Faria, André; Ghezzi, Pietro (Frontiers in Medicine, 2019)
Background. The concept that you can “boost” immunity is a popular one. Although the only evidence-based approach to this is vaccination, the lay public is exposed to a wide range of information on how to boost immunity. The aim of this study was to analyze the information available on the Internet. Methods and findings. We visited 185 webpages returned from a Google search on “boost immunity” in terms of standard indicators of health information quality (JAMA score, HONCode), classified them by typology (blogs, commercial, government, no-profit, news, professional, scientific journals) and analyzed their content in terms of disease mentioned and “booster”. Commercial and news websites represented one third of the results each. Of the 37 approaches to boost immunity recorded, the top ones were diet (77% of webpages), fruit (69%), vitamins (67%), antioxidants (52%), probiotics (51%), minerals (50%) and vitamin C (49%). Interestingly, vaccines ranked 27th, with only 12% of webpages mentioning them. Conclusions. Commercial websites are an important component of the information available to the public on the topic, and thus contribute providing biased information